Effects of prostratin on Cyclin T1/P-TEFb function and the gene expression profile in primary resting CD4(+ )T cells - Sung, Tzu-Ling (BioMed Central, 2006)
BACKGROUND: The latent reservoir of human immunodeficiency virus type 1 (HIV-1) in resting CD4(+ )T cells is a major obstacle to the clearance of infection by highly active antiretroviral therapy (HAART). Recent studies have focused on searches for adjuvant therapies to activate this reservoir under conditions of HAART. Prostratin, a non tumor-promoting phorbol ester, is a candidate for such a strategy. Prostratin has been shown to reactivate latent HIV-1 and Tat-mediated transactivation may play an important role in this process. We examined resting CD4(+ )T cells from healthy donors to determine if prostratin induces Cyclin T1/P-TEFb, a cellular kinase composed of Cyclin T1 and Cyclin-dependent kinase-9 (CDK9) that mediates Tat function. We also examined effects of prostratin on Cyclin T2a, an alternative regulatory subunit for CDK9, and 7SK snRNA and the HEXIM1 protein, two factors that associate with P-TEFb and repress its kinase activity. RESULTS: Prostratin up-regulated Cyclin T1 protein expression, modestly induced CDK9 protein expression, and did not affect Cyclin T2a protein expression. Although the kinase activity of CDK9 in vitro was up-regulated by prostratin, we observed a large increase in the association of 7SK snRNA and the HEXIM1 protein with CDK9. Using HIV-1 reporter viruses with and without a functional Tat protein, we found that prostratin stimulation of HIV-1 gene expression appears to require a functional Tat protein. Microarray analyses were performed and several genes related to HIV biology, including APOBEC3B, DEFA1, and S100 calcium-binding protein genes, were found to be regulated by prostratin. CONCLUSION: Prostratin induces Cyclin T1 expression and P-TEFb function and this is likely to be involved in prostratin reactivation of latent HIV-1 proviruses. The large increase in association of 7SK and HEXIM1 with P-TEFb following prostratin treatment may reflect a requirement in CD4(+ )T cells for a precise balance between active and catalytically inactive P-TEFb. Additionally, genes regulated by prostratin were identified that have the potential to regulate HIV-1 replication both positively and negatively.